Axotomy-induced HIF-serotonin signalling axis promotes axon regeneration in C. elegans - Tanimul Alam (Nature Portfolio, 2016)
The molecular mechanism of axon regeneration after injury is poorly understood. Here the authors show that in C. elegans, the HIF-1 transcription factor induces ectopic synthesis of serotonin in severed ‘non-serotonergic’ neurons and that serotonin activates downstream signaling pathways leading to axon regeneration.